Experimental Method on “Pseudo Delights” Artwork - Fransisca Retno Setyowati Rahardjo (IJCAS (International Journal of Creative and Arts Studies), 2019)
ABSTRACTIn 1975 Indonesian contemporary art was believed to be born and marked by the occurrence of the “Black December” event which then initiated the Gerakan Seni Rupa Baru Indonesia. Arts academy also swiftly respond to this phenomenon by putting an art experimentation course as their subject in ITB and ASRI Yogyakarta. Another example was made in 1987, a successful experimental exhibition “Pasaraya Dunia Fantasi” which was held Taman Ismail Marzuki being a headline. It is now four decades the development of experimentation medium celebrated even to other non-art disciplines. Being consider of it the author seeks to bring back the methods of the past that have been adapted to the contexts of today's problems and technological advances. In this research will be a study to develop experimentation model by using some reference logic theory such as design thinking method to produce a work. The development of contemporary art and design has not been widely recognized as an interdisciplinary area that could potentially be developed into a sophisticated and cutting-edge work. In contrast, in some academic and art academic discourses, student’s views are narrowed by thickening the barriers between art and design under the pretext of need capitalization of education. Therefore, the author tries to create a method of designing an experimentation work entitled 'Pseudo Delights'. This work has been previously executed and exhibited at the National Gallery. Pseudo Delight is a performative event specially engineered to respond to today's hyper-reality phenomenon. Where the development of information and mass media is celebrated massively. The rise of many social media applications such as Instagram, the urban communities can celebrate the exclusivity of their lives in a virtual gallery freely. As to convince others about the image of their modern life that is considered successful often the image that appears then contain excessive payload or false sign. Something paradoxical to the advancement of information technology today is presenting a lot of fake images has become the era of the death of information itself.  ABSTRAK Pada tahun 1975 seni rupa kontemporer Indonesia diyakini lahir dengan tanda hadirnya peristiwa “Black December” yang kemudian mengawali Gerakan Seni Rupa Baru Indonesia. Akademi seni juga dengan cepat merespon fenomena ini dengan menambahkan mata kuliah eksperimentas seni sebagai salah satu subjek pendidikan seni di ITB dan ASRI Yogyakarta. Contoh lain ada pada tahun 1987 ketika sebuah pameran eksperimental yang sukses "Pasaraya Dunia Fantasi" yang diadakan Taman Ismail Marzuki menjadi berita utama. Sekarang empat dekade lebih pengembangan media eksperimen telah dirayakan bahkan untuk kegiatan disiplin non-seni lainnya. Dengan mempertimbangkan hal itu penulis berusaha untuk mengembalikan metode masa lalu yang telah disesuaikan dengan konteks masalah saat ini dan kemajuan teknologi. Dalam penelitian ini akan dilakukan penelitian untuk mengembangkan model eksperimen dengan menggunakan beberapa teori logika referensi seperti merancang metode berpikir untuk menghasilkan suatu karya. Perkembangan seni dan desain kontemporer belum diakui secara luas sebagai bidang interdisipliner yang berpotensi dikembangkan menjadi karya canggih dan mutakhir. Sebaliknya, dalam beberapa wacana akademis dan seni, pandangan siswa dipersempit dengan mempertebal hambatan antara seni dan desain dengan dalih kapitalisasi kebutuhan pendidikan. Oleh karena itu, penulis mencoba membuat metode merancang karya eksperimen berjudul 'Pseudo Delights'. Karya ini sebelumnya telah dieksekusi dan dipamerkan di Galeri Nasional. Pseudo Delights adalah acara performatif yang dirancang khusus untuk merespons fenomena hiper realitas saat ini. Di mana perkembangan informasi dan media massa dirayakan secara masif. Maraknya banyak aplikasi media sosial seperti instagram, masyarakat perkotaan dapat merayakan eksklusivitas kehidupan mereka di galeri virtual secara bebas. Seperti untuk meyakinkan orang lain tentang citra kehidupan modern mereka yang dianggap sukses sering gambar yang muncul kemudian mengandung muatan berlebihan atau tanda palsu. Sesuatu yang paradoks dengan kemajuan teknologi informasi saat ini adalah menghadirkan banyak gambar palsu yang telah menjadi era kematian informasi itu sendiri.